Meningkatkan kemampuan pemecahan masalah matematis terhadap pendekatan realistic mathematics eduction (RME) berbantuan VBA excel - Hasim, Pitria; Sabandar, Jozua; Fitrianna, Aflich Yusnita (IKIP Siliwangi, 2025)
This research aims to examine the enhancement of mathematical problem-solving skills and the application of learning through the RME approach with the assistance of VBA Excel. The method used in this research is a quasi-experimental design with a pretest-posttest control group involving two groups of students: the experimental group, which received treatment through the RME approach assisted by VBA Excel, with the outcome observed being the students' mathematical problem-solving abilities. Meanwhile, the control group received instruction using the conventional approach. The population in this study is all eighth-grade students at SMP Negeri 4 Cimahi. The research sample consists of two randomly selected classes, namely the experimental class with 30 students and the control class with 30 students at SMPN 4 Cimahi. The instrument used consists of four open-ended questions assessing mathematical problem-solving abilities on the topic of the Pythagorean theorem. Data analysis was conducted using normality tests, homogeneity tests, and t-tests. The research results indicate that the Realistic Mathematics Education (RME) approach assisted by VBA Excel can enhance students' mathematical problem-solving abilities compared to the conventional approach in the learning process.